Automated Parking System using IR Sensor - G., Preethi; G., Harishankar R; S., Dravid R (IRO Journal on Sustainable Wireless Systems, 2024)
As the population grows, people face more challenging parking issues that make city life more difficult. However, automated parking systems have become a ray of hope in modern society. Urban living is entering a transformational era with these innovative solutions. Automated parking systems reduce traffic and transform the urban environment by seamlessly incorporating advanced technology into parking management. Therefore, the proposed system utilizes Arduino boards and infrared (IR) sensors to develop an automated parking system (APS) that improves urban parking efficiency, reduces traffic jams, and minimizes environmental harm. The system integrates seamlessly with existing city infrastructure, providing a cost-effective and adaptable solution. The prototype of the APS is developed and tested to ensure its ease of installation and use in urban areas.
Keywords: Smart Parking System; Urban Mobility; Arduino Board; Infrared Sensors; Traffic Congestion; Environmental Sustainability; Real-time Communication; Parking Management; Sustainable Transportation